Thickness change and deformation of custom‐made mouthguards after two years of use by Bangladeshi field hockey players. Issue 4 (23rd February 2021) - Hayashi, Kairi; Chowdhury, Ruman Uddin; Chowdhury, Nafees Uddin; Shrestha, Abhishekhi; Pradhan, Ishan; Shahrin, Sharika; Toyoshima, Yukako; Tanabe, Gen; Yoshida, Yuriko; Togawa, Kaito; Churei, Hiroshi; Ueno, Toshiaki
Abstract: Background/Aim: Sports mouthguards are effective devices that prevent dental trauma in sports activities. Players should change mouthguards on a regular basis because of thickness reduction and shape deformation. However, there is no guidance regarding the best timing to change mouthguards. The aims of this study were to analyze the thickness change and deformation of mouthguards after 2 years of use in Bangladesh field hockey players and to consider appropriate evaluation criteria. Material and Methods: Fifty‐seven field hockey players belonging to the Bangladesh Sports Education Institute participated in this study. Participants were provided with double‐layered mouthguards made of polyolefin‐based material using a vacuum‐forming machine. Mouthguards were fabricated using 2‐mm‐thick sheet as the first layer and 3‐mm‐thick sheet as the second layer. Players used the mouthguards for 2 years. Before and after using the mouthguards, the thicknesses of nine areas were measured. In addition, the lengths of five areas were used to analyze shape deformation. Results: After 2 years, the thicknesses of all measured areas had significantly reduced, and the lengths had significantly increased. Thickness reduction of the posterior‐occlusal and anterior‐incisal areas and deformation of the posterior‐buccal and posterior‐palatal areas were significantly larger than those in other measured areas. Conclusions: Mouthguards should be changed on a regular basis to minimize thickness reduction and deformation. Occlusal and incisal thickness and length of the buccal‐posterior area and the palatal‐posterior area are factors to be considered in establishing guidelines regarding the timing of mouthguard change.